A Comparison of Canal Width Changes in Simulated Curved Canals prepared with Profile and Protaper Rotary Systems : Canal Width Changes in Simulated Curved Canals - Faisal, Aisha; Farid, Huma; Ghafoor, Robia (Pakistan Journal of Health Sciences, 2022)
With advancement in the endodontic technology there is a quest to introduce root canal instruments showing superior performance by removing minimum amount of sound root dentine and retaining the original shape of the root canal. Objective: To compare the changes in the width of simulated curved canals prepared with ProFile and ProTaper rotary system. Methods: This in-vitro, Quasi Experimental study was carried out in the Dental section of The Aga Khan University Hospital. Pre and post instrumentation photographs (images) of sixty resin blocks prepared with ProFile and ProTaper rotary instruments respectively (with 1:10 magnification) were superimposed using software Adobe Photoshop 6.0. Measurements were done on print out of composite images. Measurements of change in width (resin removed) were recorded along the length of canal at 12 points. Results: Two rotary system showed statistically significant difference in simulated curved canals width after preparation. ProTaper rotary instruments showed more resin removal at the inner walls of the canal at 1, 8-12mm from the apex and more resin removal at outer wall of canal at 9-12 mm from apex. Conclusions: ProFile and ProTaper rotary files showed statistically significant difference in canal width after instrumentation. ProTaper rotary files showed more resin removal in canals towards the inner wall and coronal part of the outer wall.